2008
DOI: 10.1002/cncr.23918
|View full text |Cite
|
Sign up to set email alerts
|

Risk of radiation‐related salivary gland carcinomas among survivors of Hodgkin lymphoma

Abstract: BACKGROUND.Radiotherapy for Hodgkin lymphoma (HL) increases the risk of salivary gland carcinomas (SGC). To the authors' knowledge, however, the magnitude of the risk has not been assessed to date.METHODS.The risks of SGC among 20,928 1‐year survivors of HL who were diagnosed between 1973 and 2003 were evaluated in 11 population‐based cancer registry areas of the Surveillance, Epidemiology, and End Results (SEER) program. Observed‐to‐expected ratios (O/E) were assessed by radiation treatment, sex, age at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In our investigation, most of the cases of SGC occurred in the parotid gland, and this finding was to be expected based on results from other series (25). Our analyses showing mucoepidermoid carcinomas to be strongly associated with radiotherapy for childhood cancer are consistent with the especially strong radiation dose-response found for mucoepidermoid carcinomas seen in studies of atomic bomb survivors (7).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our investigation, most of the cases of SGC occurred in the parotid gland, and this finding was to be expected based on results from other series (25). Our analyses showing mucoepidermoid carcinomas to be strongly associated with radiotherapy for childhood cancer are consistent with the especially strong radiation dose-response found for mucoepidermoid carcinomas seen in studies of atomic bomb survivors (7).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this is the finding of Dores et al (26) who reported no significant difference in risk of SGC between male and female HL survivors, and the absence of a significant gender difference among atomic bomb survivors (7, 8) and among children irradiated with low doses to the head or neck for benign medical conditions (1). In contrast, Boukheris et al (25) reported an increased risk for SGC among women treated for HL compared with men. Given the inconsistent results, additional data are needed before any conclusions about gender differences can be drawn.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Conversely, the O/E ratio for SGC was much higher for patients who received radiotherapy for HL, similar to what was reported in an earlier study 17 ; the current analysis benefits from larger patient numbers and longer follow‐up. In the study by Boukheris et al, the authors postulate that neck radiation exposure from mantle radiation, particularly with the higher doses and “full‐mantle” fields used in the past, likely contributed to this risk. The authors report approximate (based on a mathematic phantom) doses of 32 gray (Gy), 18 Gy, and 7 Gy, respectively, to the submandibular, parotid, and sublingual glands based on a typical mantle field dose of 35 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Moreover, it has been previously reported, based on SEER data from 1973 through 2003, that survivors of HL who received radiotherapy for HL were 16.9 times more likely to develop salivary gland cancers (SGCs) compared with a matched control population. 17 In the current study, we examined population characteristics among patients with HL who later developed HNC and assessed the effect of a history of HL on survival after second primary HNC by comparing these patients with patients with a first primary HNC. We analyzed nonsalivary squamous cell carcinoma (SCC) and SGC as separate entities.…”
Section: Introductionmentioning
confidence: 99%